Emotional Communication as Complex Phenomenon in Musical Interpretation – Proposal for a Systemic Model That Promotes a Transdisciplinary Process of Self-Formation and Reflection Around Expressiveness as a Lived Experience - Fuensanta Fernández de Velazco; Eduardo Carpinteyro-Lara; Saúl Rodríguez-Luna (Journal of Systemics, Cybernetics and Informatics)

(untitled)
For a long time, expressiveness in musical performance was a question of musical performance and research. It was difficult to explain why musicians arouse aesthetic emotions in their listeners with their interpretation. Even so, was more complex to explain why the performance of the same work by various artists provoked different emotional responses in listeners. Thanks to empirical research, our understanding of this phenomenon has improved. However, these theories and discoveries have not permeated teaching practice, so they have not yet taken a new direction in music teaching. In this paper, we proposed a new approach to expressiveness in musical interpretation in a systemic and complex way. For this, we propose a systemic model that allows us to observe the dynamic behavior of the phenomenon of emotional communication in musical interpretation. Furthermore, we suggest a systemic transdisciplinary didactic proposal to encourage the performer to develop their musical identity, reinforce their sensitivity and creativity, and enrich their expression and participatory intention in interpretation.